Evaluation of oxidative stress and antioxidant status: Correlation with the severity of sepsis. (25th March 2018) - Kumar, S.; Gupta, E.; Kaushik, S.; Kumar Srivastava, V.; Mehta, S.; Jyoti, A.
Abstract: Sepsis is a condition caused by infection followed by unregulated inflammatory response which may lead to the organ dysfunction. During such condition, over‐production of oxidants is one of the factors which contribute cellular toxicity and ultimately organ failure and mortality. Antioxidants having free radicals scavenging activity exert protective role in various diseases. This study has been designed to evaluate the levels of oxidative and antioxidative activity in sepsis patients and their correlation with the severity of the sepsis. A total of 100 sepsis patients and 50 healthy controls subjects were enrolled in this study from the period October 2016 to June 2017. The investigation included measurements of oxidative enzyme, myeloperoxidase (MPO), antioxidant enzymes including superoxide dismutase activity (SOD) and catalase activity (CAT) and cytokines (TNF‐α, IL‐8 and IFN‐γ). Furthermore, the level of these activities was correlated with severity of sepsis. Augmented levels of oxidants were found in sepsis as demonstrated by DMPO nitrone adduct formation and plasma MPO level activity (1.37 ± 0.51 in sepsis vs 0.405 ± 0.16 in control subjects). Cytokines were also found to be increased in sepsis patients. However, plasma SOD and CAT activities were significantly attenuated ( P  < .001) in the sepsis patients compared with controls subjects. Moreover, inverse relation between antioxidant enzymes (SOD and CAT) and organ failure assessment (SOFA), physiological score (APACHE II), organ toxicity specific markers have been observed as demonstrated by Pearson's correlation coefficient. This study suggests that imbalance between oxidant and antioxidant plays key role in the severity of sepsis.